PERSEPSI MAHASISWA TERHADAP APLIKASI JSHO SEBAGAI MEDIA PEMBELAJARAN KANJI - Nur fadhillah; Arza Aibonotika; Nana Rahayu (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2022)
Abstrack: The progress of technology make it easier to learn Japanese, especially in the presence of applications such as electronic dictionaries. This study aims to explain students perception of the Jsho application as a kanji learning media. The method used in this research is quantitative with a descriptive approach. The data is obtained by distributing questionnaires to 30 students of the 2019, 2020, 2022 class of Japanese Language Education FKIP Riau University. The results of the questionnaire research on the Jsho application from display indicators, usage indicators, and satisfaction indicators with an average percentage of 77.75% including the criteria for strongly agree.Key Words: Jsho Application, Kanji, Perception.